The LysR-Type Transcriptional Regulator YeeY Plays Important Roles in the Regulatory of Furazolidone Resistance in Aeromonas hydrophila - Fu, Yuying; Zhang, Lishan; Wang, Guibin; Lin, Yuexu; Ramanathan, Srinivasan; Yang, Guidi; Lin, Wenxiong; Lin, Xiangmin (Frontiers in Microbiology, 2020)
Aeromonas hydrophila is an aquatic pathogen of freshwater fish. The emergence of widespread antimicrobial-resistance strains of this pathogen has caused increasing rates of fish infections. Our previous research reported that A. hydrophila yeeY, a LysR-type transcriptional regulator (LTTR), negatively regulated furazolidone (FZ) resistance. Although, it’s intrinsic regulatory mechanism is still unclear. In this study, a data-independent acquisition (DIA) quantitative proteomics method was used to compare the differentially expressed proteins (DEPs) between the ΔyeeY and wild-type strain under FZ treatment. When compared to the control, a total of 594 DEPs were identified in ΔyeeY. Among which, 293 and 301 proteins were substantially increased and decreased in abundance, respectively. Bioinformatics analysis showed that several biological pathways such as the secretion system and protein transport were mainly involved in FZ resistance. Subsequently, the antibiotics susceptibility assays of several gene deletion strains identified from the proteomics results showed that YeeY may regulate some important genes such as cysD, AHA_2766, AHA_3195, and AHA_4275, which affects the FZ resistance in A. hydrophila. Furthermore, 34 antimicrobial resistance genes (ARGs) from the bacterial drug resistance gene database (CARD) were found to be directly or indirectly regulated by YeeY. A subsequent assay of several ARGs mutants showed that ΔAHA_3222 increased the susceptibility of A. hydrophila to FZ, while ΔcysN and ΔAHA_3753 decreased the susceptibility rate. Finally, the chromatin immunoprecipitation (ChIP) PCR and an electrophoretic mobility shift assay (EMSA) have revealed that the genes such as AHA_3222 and AHA_4275 were directly and transcriptionally regulated by YeeY. Taken together, our findings demonstrated that YeeY may participate in antimicrobial resistance of A. hydrophila to FZ, which provides a new target for the development of novel antimicrobial agents in the future.